Factors influencing late-Holocene vegetation dynamics and biodiversity on Hallands Väderö, SW Sweden: A statistical evaluation. (November 2022) - Hannon, Gina E; Molinari, Chiara; Bradshaw, Richard HW
Forest composition characteristic of the Mid-Holocene has survived on Hallands Väderö, an island nature reserve off the south west coast of Sweden. Current veteran Tilia and Quercus trees contribute to a remarkably rich biodiversity of fungi, bryophytes, lichens and insects. Understanding which potential factors influence Holocene vegetation dynamics can support efforts to protect biodiversity, but the role of grazing and browsing has previously been difficult to evaluate because of the lack of long-term datasets. Palaeoecological analyses over the last c. 3000 years from a pond on the island reveal sustained presence of Quercus, Alnus, Tilia, Corylus and Ulmus, alongside increasing Fagus in recent centuries. Changes in grazing pressure have been documented since AD 1665 and a statistical approach was used to calculate the relative importance of grazing pressure, climate variability, and fire activity on the dynamics of selected taxa. Grazing was the main factor reducing population size of Fagus, Alnus, Tilia and Corylus on the island over the period AD 1665–1858, with warm winter temperatures and summer humidity having significant positive influences in the last millennium for Quercus, Alnus, Tilia and Corylus . The survival of large numbers of red-listed species is likely to be due to the continuity of large old trees, ancient forest composition and a distinctive disturbance history in a favourable climate.